INTEGRASI VIDEO SIMULASI EKONOMI DALAM PEMBELAJARAN TEORI PRODUKSI - Anggi Dwi Setyani; Tutut Suryaningsih (Universitas Islam Raden Rahmat Malang, 2026)
Economic learning, especially in production theory, requires an understanding of abstract and complex concepts. Therefore, the use of appropriate learning media is an important factor in supporting the achievement of learning objectives. This study aims to examine the application of economic simulation videos in production theory learning and their effectiveness in improving the learning process of students. The results of the study show that the integration of simulation video media can create a more meaningful learning experience through the visualization of the concrete production process, making it easier for students to understand the relationship between production factors, costs, and output. Video media also contributes to increasing students' learning motivation, active involvement, and analytical thinking skills. However, the application of simulation videos still faces a number of challenges, particularly related to teachers' readiness in mastering technology and the availability of supporting facilities. Therefore, adequate training and facilities are needed so that the use of simulation video media can be optimally implemented in economics learning.